Power Factor Correction – A Simulation Approach - Che Ros, Ziana; Nordin, Muhammad Faris; Anuar, Muhammad Abdullah; Abdul Razak, Muhammad Hazim (Penerbit UTHM, 2020)
A power factor of one or "unity power factor" is the goal of any electrical utility company since if the power factor is less than one, they have to supply more current to the user for a given amount of power used. In so doing, they incur more line losses. They also must have larger capacity equipment in place than would be otherwise necessary. As a result, an industrial facility will be charged a penalty if its power factor is much different from 1. Industrial facilities tend to have a "lagging power factor", where the current lags the voltage (like an inductor). Some industrial sites will have large banks of capacitors strictly for the purpose of correcting the power factor back toward one to save on utility company charges. The main focus of this study is to indicate how much Farad is needed to improve power factor in a selected Electrical Power System (EPS), to estimate the Capacitor bank location that need to be installed in the system on Ring Main Unit (RMU) by using POWERWORLD Software for beginners.